Microstructural characterisation of organic-rich shale before and after pyrolysis - Uvarova, Y.; Yurikov, A.; Pervukhina, M.; Lebedev, Maxim; Shulakova, V.; Clennell, B.; Dewhurst, D. (Australian Petroleum Production and Exploration Association, 2014)
Organic-rich shales, traditionally considered as source rocks, have recently become an ambitious goal for the oil and gas industry as important unconventional reservoirs. Understanding of the initiation and development of fractures in organic-rich shales is crucially important as fractures could drastically increase the permeability of these otherwise low-permeable rocks. Fracturing can be induced by rapid decomposition of organic matter caused by either natural heating, such as emplacement of magmatic bodies into sedimentary basins, or thermal methods used for enhanced oil recovery. In this work the authors study fracture initiation and development caused by dry pyrolysis of Kimmeridge shale, which is characterised with a high total organic carbon content of more than 20%. X-ray diffraction (XRD) analysis exhibits high carbonate (both calcite and dolomite) and low clay (illite) content. Field emission gun scanning electron microscopy (FEG-SEM) shows that kerogen is presented either as a load-bearing matrix or as a filling of the primary porosity with pores being of micron size. Cylindrical samples of the Kimmeridge shale are heated up to temperatures in the range of 330–430°C. High-resolution X-ray microtomographic (micro-CT) images are obtained. The microtomographic images are processed using AVIZO (Visualization Sciences Group) to identify and statistically characterise large kerogen-filled pores and pre-existing and initiated cracks. The relationship between the total area of fractures and the temperature experienced by the sample has been obtained. Total organic carbon content is determined for samples subjected to heating experiments. This approach enables a quantitative analysis of fracture initiation and development in organic-rich shales during heating.